2013
DOI: 10.4274/vhd.53825
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Assessment of the Prevalence of Hepatic Steatosis in Inactive Hepatitis B Carriers

Abstract: Re cei ved/Ge liş ta ri hi: 17.05.2013 Ac cep ted/Ka bul ta ri hi: 05.06.2013 © Viral Hepatit Dergisi, Ga le nos Ya y› ne vi ta ra f›n dan ba s›l m›fl t›r.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(4 reference statements)
0
2
1
1
Order By: Relevance
“…In the present study, HBsAg-negative patients were in a young age group, and the incidence of NAFLD was significantly higher in older patients in the same group. Previous studies have reported that male gender and advanced age are significant factors in HBV patients (6,7,15,16,17). However, in our study, we could not find a similar correlation with age in patients with positive HBsAg.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In the present study, HBsAg-negative patients were in a young age group, and the incidence of NAFLD was significantly higher in older patients in the same group. Previous studies have reported that male gender and advanced age are significant factors in HBV patients (6,7,15,16,17). However, in our study, we could not find a similar correlation with age in patients with positive HBsAg.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalence of NAFLD is 19.8% in our country (13), whereas in Western populations this rate has been reported to be between 20% and 30% (14). According to the Turkish data, NAFLD is found in 21.1-52% of inactive HBsAg carriers (6,15,16), and in 39% of CHB patients (7). In their study performed in Indonesia, Lesmana et al.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NAFLD has been rated and graded according to the USG results in many publications [9, 11, 13, 25, 26]. Overall, hepatic USG is a simple, noninvasive technique that is widely used in clinical practice to detect the fatty infiltration of the liver [27].…”
Section: Discussionmentioning
confidence: 99%
“…Bir çalışmada ultrasonografinin yağlı karaciğerdeki duyarlılığı %90,4, özgüllüğü %97,3, pozitif kestirim değeri %97,3, negatif kestirim değeri %94,8 olarak saptanmıştır (23). Ultrasonografi aynı zamanda inaktif HBV taşıyıcılarının izlenmesinde hepatoselüler karsinom taraması yanında diğer yapısal bulgular yönünden de önem taşımaktadır (24)(25)(26). Hastalarımızda ultrasonografik incelemede 10 hastada karaciğerde basit kist, 15 hastada safra kesesinde taş, 16 hastada safra kesesinde polip, 27 hastada böbrekte basit kist, 7 hastada karaciğerde hemanjiyom, 8 hastada geçirilmiş kolesistektomi ve 6 hastada ise splenomegali saptandı.…”
Section: Gereç Ve Yöntemunclassified